SOSIALISASI PRODUK DAN AKAD PT. PEGADAIAN SYARIAH DI MAJELIS TAKLIM SYABABUL ILMI CEGER CIPAYUNG - Hasbi Ash Shiddieqy; Wahyudi (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
Sharia Pegadaian which is a Business Unit of PT. Pegadaian Persero is very active in socializing its products, one of which is through the Taklim Assembly - Taklim Council and also involving educators such as lecturers. PT. Sharia Pegadaian with the Sybabul Ilmi Taklim Council and Lecturer in Islamic Economics namely Mr. Hasbi Ash Shiddieqy and Mr. Wahyudi from PT. Sharia Pegadaian Dewi Sartika Branch conducts Product and Akad socialization. The socialization was attended by 70 residents of the Ceger sub-district, Cipayung District, East Jakarta. There were also local community leaders namely Ustadz Arifin and Ustadz Imam Marzuki. The event will be held on Thursday 14 April 2022 at 16.00 – 17.15 WIB.